2020
DOI: 10.1126/sciadv.aax3223
|View full text |Cite
|
Sign up to set email alerts
|

Tracking extracellular vesicle phenotypic changes enables treatment monitoring in melanoma

Abstract: Monitoring targeted therapy in real time for cancer patients could provide vital information about the development of drug resistance and improve therapeutic outcomes. Extracellular vesicles (EVs) have recently emerged as a promising cancer biomarker, and EV phenotyping shows high potential for monitoring treatment responses. Here, we demonstrate the feasibility of monitoring patient treatment responses based on the plasma EV phenotypic evolution using a multiplex EV phenotype analyzer chip (EPAC). EPAC incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 39 publications
1
128
0
Order By: Relevance
“…Researchers utilized microfluidic devices to examine phenotypic changes in melanoma extracellular vesicles to monitor treatment response, or to quantify the proteolytic activity of MT1-MMP for monitoring of in vivo tumor progression and metastasis. 79,80 As such, it is tempting to speculate on the future of EV clinical applications in exploiting the biochemical, physical, and functional makeup of EVs to improve diagnostics and real-time monitoring of disease.…”
Section: Looking Aheadmentioning
confidence: 99%
“…Researchers utilized microfluidic devices to examine phenotypic changes in melanoma extracellular vesicles to monitor treatment response, or to quantify the proteolytic activity of MT1-MMP for monitoring of in vivo tumor progression and metastasis. 79,80 As such, it is tempting to speculate on the future of EV clinical applications in exploiting the biochemical, physical, and functional makeup of EVs to improve diagnostics and real-time monitoring of disease.…”
Section: Looking Aheadmentioning
confidence: 99%
“…Moreover, Tucci et al found that higher expression of PD-1 and CD28 existed in immune cell-secreted EVs and may predict a good response to immunotherapy in metastatic melanoma [69], providing a new source of EVs. Wang et al studied the role of several specific proteins associated with melanoma therapy and progression in EVs, including melanoma chondroitin sulphate proteoglycan (MCSP), melanoma cell adhesion molecule (MCAM), low-affinity nerve growth factor receptor (LNGFR), and receptor tyrosine-protein kinase (ErbB3) [70]. The results indicated that these particular EVs were changing in different melanoma patients during and after targeted therapy [70].…”
Section: Circulating Ev-proteins In Melanomamentioning
confidence: 99%
“…The detection and quantification of these biomarkers form a challenge due to their low amount in body fluids, the possibility of ctDNA fragmentation and instability of miRNA and RNA molecules. DNA sequencing is one of the most frequently used techniques in liquid biopsy applications; however, there is still a need for developing lower-cost and faster methods or devices that will provide increased portability, practicality, sensitivity and specificity, as well as the potential of multiplex analysis and point-of-care testing [ 21 , 22 ]. Nanomaterials have been exploited in liquid biopsy applications for signal improvement, due to the extremely low amounts of cancer ‘signature’ molecules present in body fluid samples.…”
Section: Signal Enhancement Approaches In Liquid Biopsy Applicationsmentioning
confidence: 99%